2007
DOI: 10.1074/jbc.m605741200
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Inhibitory NFκB Complexes and Phosphorylated cAMP Response Element-binding Protein Correlates with the Anti-inflammatory Activity of Complement Protein C1q in Human Monocytes

Abstract: The interaction of C1q with specific cells of the immune system induces activities, such as enhancement of phagocytosis in monocytes and stimulation of superoxide production in neutrophils. In contrast to some other monocyte activators, C1q itself does not induce pro-inflammatory cytokine production, but rather inhibits the lipopolysaccharide (LPS)-stimulated induction of certain pro-inflammatory cytokines and induces expression of interleukin-10. To investigate the molecular mechanism by which C1q exerts this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 62 publications
7
63
0
Order By: Relevance
“…It is also reported that C1q stimulation leads to the activation of predominantly p50p50 homodimers, thereby competing with transcriptionally active p65p50 and resulting in reduced proinflammatory cytokine production. 51 In our studies, we did not observe that C1q enhanced transforming growth factor-b transcription as might have been expected. This observation is consistent with a previous study that showed that HMGB1 alone can increase transforming growth factor-b expression in a RAGEdependent pathway in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 47%
“…It is also reported that C1q stimulation leads to the activation of predominantly p50p50 homodimers, thereby competing with transcriptionally active p65p50 and resulting in reduced proinflammatory cytokine production. 51 In our studies, we did not observe that C1q enhanced transforming growth factor-b transcription as might have been expected. This observation is consistent with a previous study that showed that HMGB1 alone can increase transforming growth factor-b expression in a RAGEdependent pathway in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 47%
“…It is of note that the signaling cascade seems to involve common effectors. Here, the addition of C1q to fA␤-injured neurons resulted in increased phosphorylation and nuclear translocation of CREB, similar to what was observed in nutrient-stressed neurons (10) and in monocytes (46). CREB is a transcription factor vital for long term memory and synaptic plasticity (34), neurogenesis (47)(48)(49), and induction of neurotrophic factors in the CNS (35).…”
Section: Discussionmentioning
confidence: 67%
“…One question that arises here is why Mertk , which blocked PI3K activation and Akt phosphorylation, did not decrease NF-B reporter activation. However, a further study by Tenner et al also showed nuclear inhibition of NF-B during C1q-mediated anti-inflammatory signaling and blockade of LPS signaling (51). They suggested that C1q induced CREB phosphorylation and association with p65 but also that C1q favored a dimeric p50/p50 NF-B complex that bound to B DNA elements but did not promote transcription.…”
Section: Discussionmentioning
confidence: 99%